2022
DOI: 10.3390/ijms23020944
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Etravirine, a Non-Nucleoside Reverse Transcriptase Inhibitor, via Anterior Gradient Protein 2 Homolog Degradation against Ovarian Cancer Metastasis

Abstract: Anterior gradient protein 2 homolog (AGR2), an endoplasmic reticulum protein, is secreted in the tumor microenvironment. AGR2 is a member of the disulfide isomerase family, is highly expressed in multiple cancers, and promotes cancer metastasis. In this study, we found that etravirine, which is a non-nucleoside reverse transcriptase inhibitor, could induce AGR2 degradation via autophagy. Moreover, etravirine diminished proliferation, migration, and invasion in vitro. Moreover, in an orthotopic xenograft mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
4
1
3
Order By: Relevance
“…The latter is likely due to the interaction of AGR2 secreted from cancer cells with VEGF and FGF2, a bond that eases angiogenesis and, consequently, metastasis [38]. The concentrations at which ETV showed results were 5-10 µM at different time points [30], which is slightly lower than the results obtained here for 24 and 48 h, but accordant to those obtained for 72 h, which can be attributed to different cancer cell types.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The latter is likely due to the interaction of AGR2 secreted from cancer cells with VEGF and FGF2, a bond that eases angiogenesis and, consequently, metastasis [38]. The concentrations at which ETV showed results were 5-10 µM at different time points [30], which is slightly lower than the results obtained here for 24 and 48 h, but accordant to those obtained for 72 h, which can be attributed to different cancer cell types.…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, DRV, RPV, and ETV, three antiretroviral drugs, were studied in UM-UC-5 bladder cancer cells. These drugs have been selected because they have been shown to have effects on cancer in studies found in the literature, namely ETV in ovarian cancer metastasis [ 30 ], RPV in pancreatic cancer [ 31 ], and DRV has demonstrated in silico evidence of inhibiting enzymes overexpressed in several cancer types [ 32 ]. Overall, the best drug tested in this study was ETV, in a concentration and time-dependent manner, having a relatively low IC 50 at 24 and 48 h (24.76 µM and 32.77 µM), but with the overall lowest IC 50 being at 72 h (5.923 µM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ненуклеозидный ИОТ этравирин, вызывающий деградацию AGR2 (белок эндоплазматической сети, секретируемый опухолевым микроокружением), in vitro подавлял пролиферацию, миграцию и инвазию опухолевых клеток. На моделях мышей комбинация паклитаксела с этравирином более эффективно ингибировала прогрессирование рака яичника [44]. На клетках сПКК была продемонстрирована способность ненуклеозидных ИОТ эфавиренза и невирапина инду-цировать иммуногенность опухоли и приводить к дифференцировке клеток [45].…”
Section: перспективы эпигенетического ингибирования ретроэлементов в ...unclassified